THE IMPACT OF HR ANALYTICS ON STRATEGIC DECISION-MAKING IN MODERN ORGANIZATIONS - Ivan Golar Riady; Oktavianti; Rizki Eka Putra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study explores the adoption, impact, challenges, and success factors of Human Resource (HR) analytics in modern organizations. The findings reveal that HR analytics has evolved from basic reporting to advanced predictive and prescriptive modeling, particularly in technology, finance, and healthcare sectors. Through data-driven insights, HR analytics enhances strategic decision-making in areas such as workforce forecasting, talent management, and organizational performance. However, challenges persist, including poor data quality, limited analytical skills, resistance to change, and ethical concerns related to data privacy. Successful implementation is driven by leadership commitment, a data-oriented organizational culture, and robust technological infrastructure. The study emphasizes that integrating HR analytics into strategic management not only improves efficiency and innovation but also ensures long-term alignment between human capital and organizational goals.